Os direitos e sua (in)efetividade - uma análise acerca das relações entre o poder, a ética e a práxis jurídica - Damaceno, Elenice Pires (2017)
The dogmatically organized modern Law, a normative order structured by the monopoly of state coercion, constitutes a social orderimpregnated of coercive power based on laws that compose the positive Law, legitimated by a social process of validation. This social order consists in a dispute field, in which the social conflicts considered to be relevant to the maintenance of the current social order are taken to authority appraisal. The monopoly of state coercion is composed by a hierarchically structured legal order, which uses state mechanisms and instruments, such as public institutions, that through juridical praxis, aims to make effective individual and collective rights, presented in an ideal structure dictated by the Law sources (norm, customs, general principles, jurisprudence and doctrine).This dissertation aims, through bibliographical and empirical research, to demonstrate the existing relations between ethics and power that permeate the legal praxis and that constitute the dispute field of the Law in the field of the effectiveness of Human Rights. The research problem passed through the necessity to reflect about the legal praxis realized in Brazil, the focus of the empirical research being the field of microethics (interpersonal relations) and macroethics (relations of collective interference), which was researched from the analysis of theses dealing with the legal praxis of the Brazilian Supreme Court (STF), from this research it was possible to trace the scenario regarding the structure in which is concentrated the concrete realization of human rights in the Brazilian judicial system.